Generating a Minimal Set of Templates for the Hippocampal Region in MR Neuroimages. Issue 3 (15th November 2012) - Cataldo, R.; Agrusti, A.; De Nunzio, G.; Carlà, A.; De Mitri, I.; Favetta, M.; Quarta, M.; Monno, L.; Rei, L.; Fiorina, E.; ,
<x xml:space="preserve">Abstract</x> ABSTRACT OBJECTIVES We detail a procedure for generating a set of templates for the hippocampal region in magnetic resonance (MR) images, representative of the clinical conditions of the population under investigation. METHODS The first step is robust standardization of the intensity scale of brain MR images, belonging to patients with different degrees of neuropathology (Alzheimer's disease). So similar tissues have similar intensities, even across images coming from different sources. After the automatic extraction of the hippocampal region from a large dataset of images, we address template generation, choosing by clusterization methods a small number of the extracted regions. RESULTS We assess that template generation is largely independent on the clusterization method and on the number and the clinical condition of the patients. The templates are chosen as the most representative images in a population. The estimation of the "minimum" number of templates for the hippocampal region can be proposed, using a metric based on the geometrical position of the extracted regions. CONCLUSIONS This study describes a simple and easily reproducible procedure to generate templates for the hippocampal region. It can be generalized and applied to other brain regions, which may be relevant for neuroimaging studies.